Decision Support System Rental Housing Investment In Singingi District Area: Decision Support System Rental Housing Investment In Singingi District Area - Nofri Wandi Al-Hafiz (Jurnal Mantik, 2020)
Construction and the need for houses in each region must be different based on the need, the number of jobs, access roads, and the condition of the location where the house will be built, whether or not it has fulfilled the requirements for a comfortable and safe house so that it can attract residents to occupy and rent the house. With the current problems, where in building a rental house, it can not immediately build a house, but it needs careful planning so that the price of rental homes in accordance with the desired. The decision making system using fuzzy logic can help the community to determine the appropriate area to be used as a lakasi for the construction of rental homes as a long-term investment.